2013
DOI: 10.1098/rspb.2013.1581
|View full text |Cite
|
Sign up to set email alerts
|

Increasing arboreality with altitude: a novel biogeographic dimension

Abstract: Biodiversity is spatially organized by climatic gradients across elevation and latitude. But do other gradients exist that might drive biogeographic patterns? Here, we show that rainforest's vertical strata provide climatic gradients much steeper than those offered by elevation and latitude, and biodiversity of arboreal species is organized along this gradient. In Philippine and Singaporean rainforests, we demonstrate that rainforest frogs tend to shift up in the rainforest strata as altitude increases. Moreov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
157
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 121 publications
(164 citation statements)
references
References 49 publications
(79 reference statements)
5
157
2
Order By: Relevance
“…Flattening could seriously alter the forest ecosystem and impact the survival of numerous species (Scheffers et al 2013). It is imperative to consider that our study did not focus specifically on frog arborality like Scheffers et al (2013). Therefore we cannot rule out the possibility that frog arborality peaked between 500-800 m and future studies are required to determine this.…”
Section: Turtles Family Geomydidaementioning
confidence: 99%
See 3 more Smart Citations
“…Flattening could seriously alter the forest ecosystem and impact the survival of numerous species (Scheffers et al 2013). It is imperative to consider that our study did not focus specifically on frog arborality like Scheffers et al (2013). Therefore we cannot rule out the possibility that frog arborality peaked between 500-800 m and future studies are required to determine this.…”
Section: Turtles Family Geomydidaementioning
confidence: 99%
“…We report 50 species of frogs from 20 genera and six families, 35 species of lizards from 19 genera and four families, 18 species of snakes from 12 genera and six families, and three species of turtle from three genera and three families ( Scheffers et al (2013) identified arborality (vertical stratification) as a key determinant of rainforests species richness and abundance patterns in Mount Banahaw, Phillipines and Singaporean lowlands especially for ectothermic and hydrophilic species such as frogs. They indicated that arboreal frog richness peaked between 600 m and 800 m and that increased elevation resulted in increased vertical species stratification.…”
Section: Turtles Family Geomydidaementioning
confidence: 99%
See 2 more Smart Citations
“…Moritz and Agudo (2013) reported range movements of plants and animals on mountains during rising temperatures that were counterintuitive: ranges shifted downslope and sideways indicating not all distributions are climate limited. In a similar vein two recent studies have suggested biota might use the inherent, small-scale variability in ecological systems to avoid modeled climate shifts (e.g., Scheffers et al 2013Scheffers et al , 2014. Southwestern Australia now consists of a mosaic of largely intact to highly altered ecosystems, with a long, complex evolutionary history offering a useful setting to examine opportunities for integrating resource use and conservation at a bioregional scale (Cheng et al 2003, Campbell 2008, Donovan et al 2009).…”
Section: Introductionmentioning
confidence: 99%